Feasibility of microalgal and macroalgal biomass co-digestion on biomethane production. (30th October 2022) - Sheng, Yequan; Shanmugam, Sabarathinam; Chinnathambi, Arunachalam; Salmen, Saleh H.; Ge, Shengbo; Xia, Changlei; Brindhadevi, Kathirvel
Abstract: Algal biomass is a promising candidate for biofuels/chemicals production in recent decades due to their huge availability and ease of cultivation methods when compared to terrestrial crops. Anaerobic digestion (AD) of algal biomass is viable option for green and sustainable biorefinery to produce energy and waste minimization. In this study, the feasibility of microalgal and macroalgal biomass on biomethane production and evaluated for mono-digestion and co-digestion process. The experiments resulted showed that mono-digestion gave relatively lower methane yield (MY) of 102–180 mL/g VS than co-digestion experiments. Co-digestion of microalgae and macroalgae biomass in the ratio of 2:8 provided the peak MY of 256 mL/g VS with an increment in MY over 40–70% than the individual algal biomass. The kinetic analysis showed that synergic effect of co-digestion with proper nutrient balance promoted the methane conversion yield from algal biomass with reduction in lag-phase time and overall improved process performances. Co-digestion of mixed algal strain is a feasible strategy to boost-up the performance of AD with relative easiness in real-field applications. Highlights: Microalgal and macroalgal biomass were successfully co-digested in AD process. Microalgal biomass provided least methane production. Blend of 2:8% microalgal and macroalgal biomass shortening lag-phase of AD process. Co-digestion stimulates the methane production from algal biomass over 40–70%. Peak methane yield of 256 mL/g VS obtained from co-digestion process.